Changes in Phenolic Metabolites and Biological Activities of Pumpkin Leaves (Cucurbita moschata Duchesne ex Poir.) During Blanching - Mashitoa, Florence M.; Shoko, Tinotenda; Shai, Jerry L.; Slabbert, Retha M.; Sivakumar, Dharini (Frontiers in Nutrition, 2021)
Pumpkin leaves (Cucurbita moschata Duchesne ex Poir.) are popularly consumed in sub-Saharan Africa and Asia. Blanching the leaves before drying is a method of preservation during off-season. In this study, different blanching treatments and media are used to test the changes in non-targeted phenolic compounds, antioxidant capacity (FRAP and ABTS activity), in vitro α-glucosidase activity and cell cytotoxicity of pumpkin leaves. Steam blanching in plain water led to the highest retention of total phenolic content and reduced the loss of quercetin 3-glucoside 7-rhamnoside (Rutin), kaempferol 7-neohesperidoside, isoorientin 2''-O-rhamnoside, isorhamnetin-3-O-rutinoside, quercetin 3-galactoside, coumaroyl glucaric acid, isorhamnetin-3-galactoside-6''-rhamnoside, 2-caffeoylisocitric acid, quercetin 3-galactoside 7-rhamnoside by (3.04%), (7.37%), (10.65%), (10.97%), (14.88%), (16.1%), (16.73%), (18.88%), and (23.15%) respectively, and coumaroyl isocitrate increased by 14.92%. Candidate markers, 2-O-caffeoylglucaric acid, 2-(E)-O-feruloyl-D-galactaric acid, quercetin 3-galactoside 7-rhamnoside (rutin) and unidentified compounds ( [(M-H) 677.28 and at RT 21.78] were responsible for the separation of the steam-blanched samples in plain water from the other blanching treatments. Steam blanching in plain water increased the antioxidant capacity (FRAP and ABTS activity). There were no cytotoxic effect or inhibitory effect of α-glucosidase activity detected in the raw or blanched pumpkin leaves.Thus, this study recommends steam blanching in plain water for African cuisine, and confirms it is safe to consume pumpkin leaves frequently.